Extraversion Moderates the Relationship Between the Stringency of COVID-19 Protective Measures and Depressive Symptoms - Wijngaards, Indy; Sisouw de Zilwa, Sophie C. M.; Burger, Martijn J. (Frontiers in Psychology, 2020)
From the start of the COVID-19 pandemic, psychologists are theorizing that, as compared to introverts, extraverts experience more profound negative social consequences from protective measures (e.g., travel restrictions and bans on public gatherings). As the empirical evidence for this claim is lacking, this study tested the hypothesis that extraversion moderates the relationship between the stringency of COVID-19 protective measures and depressive symptoms. Our results were based on survey data from 93,125 respondents collected in the early stages of the COVID-19 pandemic (March 20 – April 6, 2020) across 47 countries and publicly available data on measure stringency. Findings demonstrate that extraversion moderates the relationship between measure stringency in the early days of the pandemic and depressive symptoms. For introverts, measure stringency has a negative effect on depressive symptoms, while for extraverts, it has a positive, but nonsignificant effect on depressive symptoms. This study suggests that, although stringent measures help people to worry less and feel safer, the lifestyle associated with social distancing feels more natural to introverts than to extraverts.